2017
DOI: 10.1116/1.4982598
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of bovine serum albumin on silicon dioxide nanoparticles: Impact of pH on nanoparticle–protein interactions

Abstract: Bovine serum albumin (BSA) adsorbed on amorphous silicon dioxide (SiO2) nanoparticles was studied as a function of pH across the range of 2 to 8. Aggregation, surface charge, surface coverage, and protein structure were investigated over this entire pH range. SiO2 nanoparticle aggregation is found to depend upon pH and differs in the presence of adsorbed BSA. For SiO2 nanoparticles truncated with hydroxyl groups, the largest aggregates were observed at pH 3, close to the isoelectric point of SiO2 nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 60 publications
7
45
0
Order By: Relevance
“…The analysis of BSA adsorption on amorphous SiO 2 NPs revealed that coverage with this protein was the greatest at the isoelectric point of the BSA-SiO 2 complex with a value of ca. 3 ± 1 × 10 11 molecules cm −2 [41]. A previous study regarding the interaction of BSA with TiO 2 (~22 nm) and SiO 2 (~14 nm) NPs noticed a higher coverage on TiO 2 NPs, the BSA being completely unfold on TiO 2 NPs and having an extended conformation on SiO 2 NPs [42].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of BSA adsorption on amorphous SiO 2 NPs revealed that coverage with this protein was the greatest at the isoelectric point of the BSA-SiO 2 complex with a value of ca. 3 ± 1 × 10 11 molecules cm −2 [41]. A previous study regarding the interaction of BSA with TiO 2 (~22 nm) and SiO 2 (~14 nm) NPs noticed a higher coverage on TiO 2 NPs, the BSA being completely unfold on TiO 2 NPs and having an extended conformation on SiO 2 NPs [42].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Safinajafabadi and others also reported that the colloidal stability was enhanced by the adsorption of saccharides including glucose, maltose, and dextrin [46]. Protein (bovine serum albumin) adsorption can also enhance the dispersibility of SiO2 nanoparticles near the isoelectric point [47]. In general, the adsorption of organic matter forms a steric barrier over the particles, leading to the colloidal stabilization.…”
Section: Effects Of Eps On Aggregation and Sedimentationmentioning
confidence: 99%
“…Multiple articles have extensively reported on the BSA molecules sorption phenomenon at different interfaces such as gold (Dennison et al, 2017), mica (Fitzpatrick et al, 1992), silicon (Jachimska et al, 2016;Givens et al, 2017), and cellulose (Mohan et al, 2014;Lombardo et al, 2017). The adsorbed BSA molecule's conformation and the topology of the formed layer are strongly affected by pH, ionic strength and temperature.…”
Section: Introductionmentioning
confidence: 99%